A new gal in town: a systematic review of the role of galanin and its receptors in experimental pain - Rodrigues, Diana Marina Fonseca (2022)
Galanin is a neuropeptide expressed in a small percentage of sensory neurons of the dorsal root ganglia and the superficial lamina of the dorsal horn of the spinal cord. In this work, we systematically reviewed the literature regarding the role of galanin and its receptors in nociception at the spinal and supraspinal levels, as well as in chronic pain conditions. The literature search was performed in PubMed, Web of Science, Scopus, ScienceDirect, OVID, TRIP, and EMBASE using “Galanin” AND “pain” as keywords. Of the 1379 papers that were retrieved in the initial search, we included a total of 141 papers in this review. Using the ARRIVE guidelines, we verified that 89.1% of the works were of good or moderate quality. Galanin shows a differential role in pain, depending on the pain state, site of action, and concentration. Under normal settings, galanin can modulate nociceptive processing through both a pro- and anti-nociceptive action, in a dose-dependent manner. This peptide also plays a key role in chronic pain conditions and its antinociceptive action at both a spinal and supraspinal level is enhanced, reducing animals’ hypersensitivity to both mechanical and thermal stimulation. Our results highlight galanin and its receptors as potential therapeutic targets in pain conditions.